USE OF MODERN TECHNOLOGIES AND THEIR EFFECTIVENESS IN TEACHING FOREIGN LANGUAGES - Bahrom qizi, G‘aniyeva Barchinoy (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The role of technology in education has dramatically evolved, particularly in the domain of foreign language instruction. General Background: As globalization accelerates, the demand for effective foreign language learning methodologies has intensified. Specific Background: Traditional language teaching methods, often characterized by rote memorization and passive learning, may not adequately meet the needs of today’s diverse learners. Knowledge Gap: While various studies have highlighted the potential benefits of integrating technology into language education, there remains a lack of comprehensive analysis comparing these modern approaches to traditional methods in terms of effectiveness. Aims: This article aims to evaluate the effectiveness of modern technologies in foreign language teaching, emphasizing their advantages over conventional teaching methods. Results: Findings indicate that the integration of technology, such as interactive software, mobile applications, and online resources, significantly enhances student engagement, motivation, and language acquisition outcomes. Novelty: This study contributes to the existing literature by providing empirical evidence on how specific technological tools can foster active learning environments, promoting better retention and practical language use. Implications: The results underscore the necessity for educators to adopt technology-driven strategies in their teaching practices, as these innovations can lead to more effective and personalized language learning experiences, preparing learners for a globalized world.